'A little more courageous': cultural recognition and histories of migration and diversity at the Immigration Museum, Melbourne. (2nd January 2020) - McKernan, Amy
ABSTRACT: The Immigration Museum in Melbourne, Australia illustrates the increasing attention to working for social change and cultural recognition in museums throughout the world; its exhibitions are structured to move visitors towards understanding of and positive regard for cultural difference. There are, however, two distinct 'phases' or approaches to working towards what Fraser describes as recognitive justice in the Museum. Early exhibitions emphasised narratives of individual experience, humanising migrants, refugees and asylum-seekers through a sense of 'connection', while the most recent permanent exhibition, Identity: Yours, Mine, Ours, confronts visitors with a much more openly anti-racist stance. This paper argues that this recent exhibition represents a shift to a more unapologetically 'activist' role for the Immigration Museum, which has implications for the kind of cultural recognition sought.